Elevated Plasma Endothelin-1 Levels in Normal Tension Glaucoma and Primary Open-Angle Glaucoma: A Meta-Analysis - Shengjie Li; Aiping Zhang; Wenjun Cao; Xinghuai Sun (Journal of Ophthalmology)
Purpose. The aim of this meta-analysis was to clarify the association between the plasma endothelin-1 level and the risks of normal tension glaucoma (NTG) and primary open-angle glaucoma (POAG). Methods. Relevant publications were collected from three databases including PubMed, EMBASE, and the Web of Science through December 31, 2015. In this study, the terms “(endothelin OR ET) AND glaucoma” were searched. Review Manager 5.2 was used to process the data. Results. Seven studies (212 cases, 164 controls) were included for the NTG analysis. The mean plasma endothelin-1 level in the NTG subjects was 0.60 pg/mL (p=0.02, 95% CI: 0.17–1.04) higher than that of the healthy controls. Six studies (160 cases, 174 controls) were included for the POAG analysis, and the endothelin-1 level was 0.63 pg/mL (p=0.007, 95% CI: 0.12–1.15) higher in the POAG subjects than in the healthy controls. Additionally, two studies influenced the meta-analysis results regarding the association of plasma endothelin-1 with POAG by sensitivity analysis, and the probability of publication bias was low. Conclusions. The observation that NTG and POAG subjects showed significantly elevated endothelin-1 plasma concentrations suggests that a higher plasma level of endothelin-1 might increase the risk of NTG and POAG development.